-0.8x-0.6+0.2x=12-4x

Simple and best practice solution for -0.8x-0.6+0.2x=12-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.8x-0.6+0.2x=12-4x equation:


Simplifying
-0.8x + -0.6 + 0.2x = 12 + -4x

Reorder the terms:
-0.6 + -0.8x + 0.2x = 12 + -4x

Combine like terms: -0.8x + 0.2x = -0.6x
-0.6 + -0.6x = 12 + -4x

Solving
-0.6 + -0.6x = 12 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-0.6 + -0.6x + 4x = 12 + -4x + 4x

Combine like terms: -0.6x + 4x = 3.4x
-0.6 + 3.4x = 12 + -4x + 4x

Combine like terms: -4x + 4x = 0
-0.6 + 3.4x = 12 + 0
-0.6 + 3.4x = 12

Add '0.6' to each side of the equation.
-0.6 + 0.6 + 3.4x = 12 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + 3.4x = 12 + 0.6
3.4x = 12 + 0.6

Combine like terms: 12 + 0.6 = 12.6
3.4x = 12.6

Divide each side by '3.4'.
x = 3.705882353

Simplifying
x = 3.705882353

See similar equations:

| -6x+2-x=2 | | -17-2x=-39 | | 6+x-1+2=7x-5-4x | | -15z=24z+36 | | Fx-gx=z | | 28x+27= | | 2((-8)-2)+8= | | 3x(2x+20)=4x-20 | | -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m |

Equations solver categories